Postponement of general elections due to emergencies: a comparative study of Indonesia, Malaysia, Myanmar, and Cambodia - Muhammad Erfa Redhani; Ridwan Ridwan; Sri Hastuti Puspitasari; Ahmad Siboy (Legality : Jurnal Ilmiah Hukum, 2025)
This article examines and analyses the regulations regarding the postponement of elections in various countries, especially those that have postponed elections and countries whose constitutions regulate the postponement of elections. This study employed normative legal research methods with statutory, conceptual, and comparative approaches. Primary legal materials used in this article consist of laws and regulations relating to general elections and the constitutions of various countries, while secondary legal materials were garnered from books and journals on general elections and emergency law. The analysis indicates that in the countries studied, the postponement of elections may occur in emergencies or when the countries are in danger. Several countries like Indonesia and Malaysia do not regulate postponement of elections in their constitutions, but Myanmar and Cambodia do. The findings of this study indicate that postponing the election should be done only in a couple of months (Time-limited postponement) due to external factors (such as natural disasters) and for humanitarian rescue. This research recommends giving the president the authority to propose the postponement of the election on the proposal of the General Election Commission (KPU), which then seeks approval from the People's Consultative Assembly (MPR). Finally, the role of the Constitutional Court is needed to assess whether the reasons for postponing the election align with the idea of the proposed election delay regulation criteria included in the 1945 Constitution.